On the Bertold Spuler Collection Found in the Library of ISTAC - Wolf-Gazo, Ernest (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
On the Bertold Spuler Collection Found in the Library of ISTAC